Reinventing virtual events : how to turn ghost webinars into hybrid go-to-market simulations that drive explosive attendance /: how to turn ghost webinars into hybrid go-to-market simulations that drive explosive attendance. (2022) - Michael, Justin; Nimchinski, Julia
No abstract available